Ecosystems and biomes - AIMS Multimedia (Chatsworth, CA : AIMS Multimedia, 2001)
Explained about ecosystems and biomes in ocean, tropical, mountain, forest, desert, rain forest, and also human influence on environment
Installation guide : Macintosh, drag folder to hard drive, the double click on the program icon ; Windows, run'INSTALLE.EXE' from the cd-rom, then double click the program icon
Title from disc label
Keywords: Biotic communities -- Juvenile literature; Ecology -- Juvenile literature; Population biology -- Juvenile literature